2016
DOI: 10.1016/j.jmmm.2015.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the behavior of CuSe 2 O 5 compound in high magnetic fields

Abstract: Based on analytical and numerical approaches, we investigate thermodynamic properties of CuSe2O5 at high magnetic fields which is a candidate for the strong intra-chain interaction in quasi one-dimensional (1D) quantum magnets. Magnetic behavior of the system can be described by the 1D spin-1/2 XXZ model in the presence of the Dzyaloshinskii-Moriya (DM) interaction. Under these circumstances, there is one quantum critical field in this compound. Below the quantum critical field the spin chain system is in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…In addition, the energy spectrum is gapless. Based on the recent studies, it is suggested that the Wilson ratio, R W = 4 3 ( πkB gµB ) 2 χ CV /T , is a crucial parameter for characterizing the LL region [5][6][7][8][9][10][11] . In this relation, χ is the magnetic susceptibility and C V is the specific heat.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the energy spectrum is gapless. Based on the recent studies, it is suggested that the Wilson ratio, R W = 4 3 ( πkB gµB ) 2 χ CV /T , is a crucial parameter for characterizing the LL region [5][6][7][8][9][10][11] . In this relation, χ is the magnetic susceptibility and C V is the specific heat.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com essa proposta, no modelo clássico de Heisenberg, além das interações escalares típicas do ferrromagnetismo, em determinadas circunstâncias devem ser adicionadas "interações quirais" [8], provenientes de um produto vetorial entre duas variáveis de spin em sítios vizinhos, cujo resulado é projetado ao longo de um eixo. Nesse trabalho vamos nos concentrar em modelos simplificados com a adição dessas interações do tipo Dzyaloshinskii-Moriya (DM), que são bem menos estudados na literatura, embora tenham interesse crescente em magnetismo, e certamente possam ser generalizados para dar conta do comportamento de sistemas bem mais gerais da física dos materiais [9] [10] [11] . Embora o modelo ANNNI tenha sido muito explorado, ainda há espaço para analisar os modelos do tipo Dzyaloshinskii-Moriya (DM), que constituem o tema dessa dissertação.…”
Section: Introductionunclassified